Optimal dynamic scale and structure of a multi-pollution economy - Baumgärtner, Stefan; Jöst, Frank; Winkler, Ralph (University of Lüneburg Working paper series in economics, 2007)
We analyze the optimal dynamic scale and structure of a two-sectoreconomy, where each sector produces one consumption good and one specific pollutant. Both pollutants accumulate at different rates to stocks which damage the natural environment. This acts as a dynamic driving force for the economy. Our analysis shows that along the optimal time-path (i) the overall scale of economic activity may be less than maximal; (ii) the time scale of economic dynamics (change of scale and structure) is mainly determined by the lifetime of pollutants, their harmfulness and the discount rate; and (iii) the optimal control of economic scale and structure may be non-monotonic. These results raise important questions about the optimal design of environmental policies.- Ökonomie <Begriff> , Ökologie , Emission , Wertpapieremission, dynamic economy-environment interaction , multi-pollutant emissions , non-monotonic control , optimal scale , stock pollution
Parallel als Druckausg. erschienen
Keywords: Arbeitspapier; Graue Literatur